Effects of thermal hydrolysis on the metabolism of amino acids in sewage sludge in anaerobic digestion - Chen, Sisi; Dong, Bin; Dai, Xiaohu; Wang, Hongyang; Li, Ning; Yang, Dianhai (Waste management (Elmsford), 2019)
•Amino acids were decomposed evidently by THP at 120 °C (8.9%) and 160 °C (26.7%).•Amino acids degradation in AD was promoted largely via decomposition during THP.•Varied THP temperature changed dominating bacteria utilizing amino acids in AD.•120 °C played little role in promoting amino acids metabolic pathways during AD.•160 °C effectively enhanced amino acids metabolism via Stickland pathway during AD. Three semi-continuous anaerobic digesters with raw sludge (R1) or thermally hydrolyzed sludge (120 °C (R2) or 160 °C (R3)) were operated to investigate the effects of thermal hydrolysis on the metabolism of amino acids during high solid anaerobic digestion with sewage sludge. Thermal hydrolysis pretreatment (THP) decomposed protein in terms of hydrolytic amino acid in raw sludge by 8.90% and 26.69% under 120 °C and 160 °C, respectively. The decomposition of amino acids during THP was the main contributor to the final enhanced amino acids degradation in sewage sludge with THP after anaerobic digestion. The dominating bacterial genera related to amino acids degradation in R2 and R3 shifted to Fastidiosipila and Proteiniphilum/Tissierella, respectively, from Gelria in R1, influencing the utilization of amino acids, especially glutamic acid, glycine and proline. Different from 120 °C, THP at 160 °C played an important role in promoting amino acid metabolism during AD through the Stickland pathway by the bacteria belonged to order Clostridiales.